PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PADA MATERI MEMBIASAKAN PERILAKU TERPUJI MELALUI STRATEGI PREDICTION GUIDE SISWA KELAS III SDN 003 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Hasniati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This research is motivated by the poor performance of student learning, especially on the subjects of PAI. For that research by applying the prediction strategy guide. This study aims to improve learning outcomes PAI. This study is a class action, which was held in SDN 003 Pagaran Tapah Darussalam, the subject of this research is class III with a number of 18 students. This research was conducted in July to finish. This study was conducted in two cycles, each cycle consists of four stages: planning, implementation, observation, and reflection. The study states that PAI learning outcomes of students has increased in each cycle At the beginning of the data on average student learning outcomes was 56.7% in the medium category. In the first cycle of student learning outcomes has reached 63.9%, in the second cycle, student learning outcomes achieved quite satisfactory to reach 73.3%. This situation shows that the improvement of learning on the subjects of PAI through your prediction strategy was successful, with the thoroughness of individuals and groups of up to 70%.